Pertimbangan Hakim terhadap Pembebanan Nafkah ‘Iddah dan Mut’ah Pasca Cerai Talak bagi Istri yang Nusyuz - Sitrotul Fitri Munawaroh; Puspasari; Murniati (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2026)
‘Iddah and mut’ah nafkah are obligations that a husband must provide to his wife following a talak divorce. However, this obligation is waived if the divorce occurs due to the wife’s disobedience (nusyuz). Nevertheless, this study found a case at the Sumber Religious Court in which the judge ruled that an ex-wife, who had been divorced due to nusyuz, was still entitled to receive ‘iddah and mut’ah nafkah. In practice, not all courts render decisions in the same way. Based on this inconsistency, the author was motivated to conduct research entitled: Judges’ Considerations in Imposing ‘Iddah and Mut’ah Nafkah in Post-Talak Divorce for a Nusyuz Wife: A Maslahah Mursalah Perspective (Case Study of Decision No. 709/Pdt.G/2020/PA.Sbr). This study aims to explore the judicial reasoning behind granting ‘iddah and mut’ah nafkah to a nusyuz wife in the talak divorce case No. 709/Pdt.G/2020/PA.Sbr. The research employs a qualitative method by combining two types of data: field research through interviews and library research from books and journal articles. Data collection techniques used in this study include interviews and documentation, particularly interviews with the presiding judge at the Sumber Religious Court. All collected data were then reduced, presented, and concluded using descriptive analysis techniques. The study found that the judge’s decision to grant ‘iddah and mut’ah nafkah was based on the consideration that the divorce was not solely due to the wife’s disobedience, but also due to the husband’s negligence in fulfilling his financial obligations. Furthermore, the husband voluntarily agreed and was willing to provide the nafkah. From the perspective of maslahah mursalah, the judge’s consideration in granting such nafkah to a nusyuz wife is deemed permissible (mubah) and does not contradict Islamic legal principles. This aligns with the principle of maslahah mursalah, which holds that harm must be prevented through any available means.